2022
DOI: 10.3989/mc.2022.292722
|View full text |Cite
|
Sign up to set email alerts
|

Mix design and physical and mechanical properties of pervious concretes

Abstract: Fast-growing climate changes are known to have diverse impacts worldwide, even in large cities. Pervious concrete can be a successful safety solution for increasingly frequent heavy rains and floods. This study focuses on achieving an optimized pervious concrete within the scope of international standards by analyzing concretes made with different W/C ratios and vibration times. The results of the study show the strong influence of parameters such as porosity, permeability, and mechanical strengths. Concrete w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The Vebe method was used earlier in the studies [ 41 , 42 , 43 ] to determine the workability of pervious concrete mixes. Ximenes et al [ 41 ] used a standardized vebe method to characterize the workability of fresh mixes of pervious concrete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vebe method was used earlier in the studies [ 41 , 42 , 43 ] to determine the workability of pervious concrete mixes. Ximenes et al [ 41 ] used a standardized vebe method to characterize the workability of fresh mixes of pervious concrete.…”
Section: Discussionmentioning
confidence: 99%
“…The Vebe method was used earlier in the studies [ 41 , 42 , 43 ] to determine the workability of pervious concrete mixes. Ximenes et al [ 41 ] used a standardized vebe method to characterize the workability of fresh mixes of pervious concrete. Authors reported vebe time ranged from 6.17 to 9.67 s, decreasing with an increase in water to water-to-cement ratio of the mixes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the ratios of cement and aggregate used in SNI 03-2834-2000 and SNI 7656:2012 mix methods were 1:3,77 and 1: 4,74. Several factors have caused the difference in the proportions of the mixture, including the differences in determining the water-cement ratio, concrete weight and aggregate amount [11]. The maximum water-cement ratio (w/c) in SNI 03-2834-2000 mix method was set at 0,462 for outdoor concrete, which resulted in a smaller amount of cement for almost the same amount of water.…”
Section: Analysis Of Mixed Design Methods Between Sni 03-2834-2000 An...mentioning
confidence: 99%
“…The maximum water-cement ratio (w/c) in SNI 03-2834-2000 mix method was set at 0,462 for outdoor concrete, which resulted in a smaller amount of cement for almost the same amount of water. The w/c ratio of SNI 7656:2012 was determined at 0.5 for ordinary structures that were not protected in moderate weather, the amount of cement was more for almost the same amount of water [11], [7], [15].…”
Section: Analysis Of Mixed Design Methods Between Sni 03-2834-2000 An...mentioning
confidence: 99%